The African times and Orient review : a monthly journal devoted to the interests of the coloured races of the world - Duse Mohamed; British Library; Adam Matthew Digital (Adam Matthew Digital, 1912)
This periodical covers politics, literature, art and commerce, A striking illustrative design by Walter Crane depicting Concordia dominates the cover page. Much emphasis is placed upon promoting the common fundamental interests of white and coloured peoples. It is a publication produced by coloured people reflecting their opinions and stating their aims and desires. Vol. 5, no. 5 (new series) includes an article criticising the British political system and British rule in India: Indian notes: Is India more fit for self-government, or England?